Downregulation of the Glo1 Gene Is Associated with Reduced Adiposity and Ectopic Fat Accumulation in Spontaneously Hypertensive Rats - Šilhavý, Jan; Malínská, Hana; Hüttl, Martina; Marková, Irena; Oliyarnyk, Olena; Mlejnek, Petr; Šimáková, Miroslava; Liška, František; Kazdová, Ludmila; Moravcová, Radka; Novotný, Jiří; Pravenec, Michal (Antioxidants (Basel, Switzerland), 2020)
Methylglyoxal (MG), a potent precursor of advanced glycation end-products (AGE), is increased in metabolic disorders such as diabetes and obesity. MG and other dicarbonyl metabolites are detoxified by the glyoxalase system in which glyoxalase 1, coded by the Glo1 gene, serves as the rate-limiting enzyme. In this study, we analyzed the effects of Glo1 downregulation on glucose and lipid metabolism parameters in spontaneously hypertensive rats (SHR) by targeting the Glo1 gene (SHR-Glo1+/- heterozygotes). Compared to SHR wild-type animals, SHR-Glo1+/- rats showed significantly reduced Glo1 expression and lower GLO1 activity in tissues associated with increased MG levels. In contrast to SHR controls, SHR-Glo1+/- rats exhibited lower relative weight of epididymal fat, reduced ectopic fat accumulation in the liver and heart, and decreased serum triglycerides. In addition, compared to controls, SHR-Glo1+/- rats showed reduced serum insulin and increased basal and insulin stimulated incorporation of glucose into white adipose tissue lipids (lipogenesis). Reduced ectopic fat accumulation in the heart was associated with significantly increased pAMPK/AMPK ratio and GLUT4 activity. These results provide evidence that Glo1 downregulation in SHR is associated with reduced adiposity and ectopic fat accumulation, most likely mediated by AMPK activation in the heart.
Keywords: AMPK; insulin resistance; GLUT4; heart; spontaneously hypertensive rat; adipose tissue; methylglyoxal; Glo1 gene knockdown